INTEGRASI KURIKULUM TERPADU-ANALISIS IMPLEMENTASI DI SMAS IT UTSMAN BIN AFFAN MUARO JAMBI - Irawan, Dedy; Azmi, Ulul; Munandar, Aris (STKIP Pesisir Selatan, 2025)
This study analyzes the integration of a unified curriculum at SMAS IT Utsman bin Affan Muaro Jambi, focusing on its implementation strategies and challenges. Using a qualitative case study approach, data were collected through interviews, observation, and documentation, and analyzed using the Miles and Huberman model. The findings show that curriculum integration is carried out by combining the National Curriculum, the Diniyah Curriculum, and the Tahfidz Program within the ABATA framework—Aqidah (faith), Bahasa (language), Akhlak (ethics), Tahfidz (Qur’an memorization), and Academics. This integration is implemented comprehensively in both classroom learning and dormitory life, supported by the boarding school system and the role of musyrifah (female mentors). The ABATA model effectively enhances academic achievement, language proficiency, memorization attainment, and the development of students’ religious character. Challenges include teachers’ limited competencies, dense schedules, and time management between academic and tahfidz activities. The school addresses these issues through teacher training, the establishment of an integrated curriculum team, and schedule restructuring. The study concludes that ABATA effectively fosters knowledgeable, faithful, and virtuous female students.